Cloning of Thermostable DNA Polymerase Gene from a Thermophilic Brevibacillus sp. Isolated from Sikidang Crater, Dieng Plateu, Central Java - Lucia Dhiantika Witasari; Irfan Dwidya Prijambada; Jaka Widada; Dionysius Andang Arif Wibawa (Indonesian Journal of Biotechnology, 2010)
Thermostable DNA polymerase has an important role for amplifying small amount of DNA through polymerase chain reaction (PCR). Thermophillic bacteria Brevibacillus sp. was isolated from Sikidang Crater, Dieng Plateu, Central Java. Previous study showed that crude protein of the isolate could be used in PCR. Unfortunately, like most native thermostable enzymes, the thermostable DNA polymerase of the isolate is synthesized in a very low level and therefore is cumbersome to purify. The purpose of this research is to clone thermostable DNA polymerase gene of the isolate. The DNA polymerase gene was amplified by means of PCR using spesific primers. The amplified fragment was then isolated, purified, and ligated into the pGEM-T cloning vector. The recombinant plasmid was then transformed to competent E. coli JM109 cells using heat shock method. The cloned thermostable DNA polymerase gene from the thermophilic isolate was then characterized for its nucleotide base sequence. The result showed that the DNA Pol I gene was successfully be amplified from the isolate DNA genom, resulting in ± 2,7 kb DNA fragment in length. Sequence analysis of segment of targeted gene showed high similarity to that of thermostable DNA polymerase genes from other Bacillus.Key words : Thermostable DNA Pol I, Brevibacillus sp., PCR, cloning